Are research-policy engagement activities informed by policy theory and evidence? 7 challenges to the UK impact agenda. Issue 3 (3rd July 2021) - Hopkins, Anna; Oliver, Kathryn; Boaz, Annette; Guillot-Wright, Shannon; Cairney, Paul
Abstract: "Impact" describes how research informs policy and societal change, and "impact agenda" describes strategies to increase engagement between research and policymaking. Both are notoriously difficult to conceptualize and measure. However, funders must find ways to define and identify the success of different research-policy initiatives. We seek to answer, but also widen, their implicit question: in what should we invest if we seek to maximize the impact of research ? We map the activities of 346 organizations investing in research-policy engagement. We categorize their activities as belonging to three "generations" fostering linear, relational, and systems approaches to evidence use. Some seem successful, but the available evidence is not clear and organizations often do not provide explicit aims to compare with outcomes. As such, it is difficult to know where funders and researches should invest their energy. We relate these findings to studies of policy analysis, policy process research, and critical social science to identify seven key challenges for the "impact agenda". They include: clarify the purpose of engagement, who it is for, if it is achievable in complex policymaking systems, and how far researchers should go to seek it. These challenges should help inform future studies of evidence use, as well as future strategies to improve the impact of research.